Studies in law, politics, and society. Vol. 55 - Sarat, Austin (Studies in law, politics, and society., 2011)
This volume Studies in Law, Politics and Society contains a symposium on indigenous peoples in Latin America. It examines the ways rights are negotiated between those groups and the states in which they live. The articles in the symposium show the different ways the complex politics of rights play out in Latin American nations. They ask us to consider the way context is reflected in the political and legal life of indigenous peoples, and they consider various theoretical paradigms for understanding rights.